Biological and ecological aspects of the spectacled bear (Tremarctos ornatus, Ursidae) in the Ecuadorean Andean Zone and conservation perspectives under the landscape species approach - Sandoval Guillén, Pablo (2019)
The Andean bear (Tremarctos ornatus) has inhabited South America for more than five million years, and he is the only living representative of the short-nosed bears, a group that only lived on the American continent. In Ecuador he is considered an endangered species, mainly because the loss of natural habitats in the Andes, due to the pressure of productive anthropic activities (mainly, livestock and agriculture) and extraction of natural resources. This bear is a mammal that needs large areas to eat and find a mate. The Andean bear is important for cloud forests and paramos due to his efficient role as seed scatter. In this work, the’landscape species’ theoretical approach is applied in order to propose activities to conserve the Andean bear and the places that inhabits. This approach also allows to evaluate in a systematic way the quality of the landscape in terms of biological requirements of the species (here, Tremarctos ornatus) and the landscape human uses; likewise, it also considers the size and limits of the conservation area and its internal variation.